What is scaling? - Bohan, Sarah; Tippmann, Esther; Levie, Jonathan; Igoe, Josephine; Bowers, Blake (Journal of Business Venturing, 2024)
As ‘scaling’ has gained significant attention from different stakeholders, multiple definitions have emerged, endangering the legitimacy of the area as a distinct field of inquiry. Using a mathematics perspective, we define scaling in the business context as a time-limited process of exponential growth. We then identify drivers of scaling and show that scaling for competitive advantage requires increasing returns to scale in input-output relationships (superlinear scaling). This is followed by the application of graph theory, supported with findings from a Delphi study, to demonstrate why scaling requires internal transformation. Finally, we discuss our definition's uniqueness, how it can be operationalized, and opportunities for future research.